5k-2k+2k=3k+15-17

Simple and best practice solution for 5k-2k+2k=3k+15-17 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 5k-2k+2k=3k+15-17 equation:


Simplifying
5k + -2k + 2k = 3k + 15 + -17

Combine like terms: 5k + -2k = 3k
3k + 2k = 3k + 15 + -17

Combine like terms: 3k + 2k = 5k
5k = 3k + 15 + -17

Reorder the terms:
5k = 15 + -17 + 3k

Combine like terms: 15 + -17 = -2
5k = -2 + 3k

Solving
5k = -2 + 3k

Solving for variable 'k'.

Move all terms containing k to the left, all other terms to the right.

Add '-3k' to each side of the equation.
5k + -3k = -2 + 3k + -3k

Combine like terms: 5k + -3k = 2k
2k = -2 + 3k + -3k

Combine like terms: 3k + -3k = 0
2k = -2 + 0
2k = -2

Divide each side by '2'.
k = -1

Simplifying
k = -1

See similar equations:

| 15w-20=-14w | | 9.95+0.30+35=c | | 4/n+2=7-n | | 2n/3-5/11=29/33 | | T(x)=200-200x+60x^2 | | 2(3x-4)=5-x | | -4x^2-3x-16=-2x^2-2x-4 | | x/7-4=-9 | | 1=v+2/5+v-3/6 | | 4x+6+19-x+3x-1=3x-7.5 | | 2.5(x+15)=662.5 | | 1/3v+12=5 | | -92-2x-4x=52 | | 3(x+5)=5(x+3) | | 2.5(x+15)=412.5 | | 4x^3-6x^2+8x=0 | | 0.1(x+100)+1.3x=53 | | 36=-2(22-m)+4(m-4) | | -23=n+11 | | -16-5n=-7(-6+8n)+3 | | 35-(x-1)=-7(5-x)+28x | | -8x+-12=-44 | | 6x-9=6(x+7) | | 6/b-1=9/1 | | 6x+36/35x+20/3x+18/7x+4 | | 2(x+3)=8(x-2)-2 | | N-13+6=8 | | -16-5n=(-6+8n)+3 | | 3x-5+2=20 | | -9+12x=75 | | -25+7x-4x=53 | | (4p^-5/p^5)^3 |

Equations solver categories